Research progress on ferroptosis in diabetic kidney disease - Wu, You; Chen, Yan (Frontiers in Endocrinology, 2022)
Ferroptosis is a newly discovered form of cell death that differs from other forms of regulated cell death at morphological, biochemical, and genetic levels, and is characterized by iron-dependent accumulation of lipid peroxides. Ferroptosis is closely related to intracellular metabolism of amino acids, lipids, and iron. Hence, its regulation may facilitate disease intervention and treatment. Diabetic kidney disease is one of the most serious complications of diabetes, which leads to serious psychological and economic burdens to patients and society when it progresses to end-stage renal disease. At present, there is no effective treatment for diabetic kidney disease. Ferroptosis has been recently identified in animal models of diabetic kidney disease. Herein, we systematically reviewed the regulatory mechanism of ferroptosis, its association with different forms of cell death, summarized its relationship with diabetic kidney disease, and explored its regulation to intervene with the progression of diabetic kidney disease or as a treatment.